Association Between Family Support and Post-Stroke Activity of Daily Living Autonomy - Esa Karunia (Universitas Airlangga, 2017)
Nowadays stroke is a disease that caused the death of the fifth highest in the United State and the second at the age of 60 year old. Stroke caused some disability impact that can affect or interfere person when doing Activity Daily Living (ADL). On the otherhand, stroke also caused deprresion, so it takes a family to support stroke patients can perform the activity. Therefore, researcher investigated the relationship between family support with ADL post stroke. This research included observational studies, the design of the study was cross-sectional design. Sample was calculated using simple random sampling's formula, and the result was 47 people. Reserch conducted at the medical rehabilitation of RSU Haji Surabaya in June-July 2015. The independent variables in this study werw age, gender, occupation, and family support, while the dependent variable was ADL independent of post-stroke. Data analysis using Chi-Square with a value of 0,05. The study showed the majority of respondent had a stroke aged 43-61 years, male sex, and didn't work. Based on analysis using Chi-Square, there was a relationship between family support with ADL independent of post-stroke (p=0,018<0,05), but there was no relationship between age, sex and occupation with ADL independent of post-stroke with each p=0,197, p=0,271, and p=0,501. Most of respondents got a good family support, so that respondents can be nore independent in activities. It was hoped that family to continue to provide positive support to respondents. Keywords: Family support, Independence, Activity Daily Living, ADL, Post-stroke